2022
DOI: 10.3390/jcm11123325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intragastric Botulinum Type A Injection Combined with a Low-Calorie High-Protein Diet in Adults with Overweight or Obesity

Abstract: (1) Background/aims: Intragastric botulinum toxin A injection (IGBI) combined with diet control is a new and effective weight loss method for grade 2 obese patients. However, the application of IGIB on overweight or obese adults still needs further research to confirm its efficacy. (2) Methods: We retrospectively collected medical data from 1 July 2021 to 1 January 2022 from a total of 71 patients without diabetes who participated in the bariatric clinic with a body mass index (BMI) > 25 kg/m2. Forty-nine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Another retrospective study reported significant reduction in weight loss when injecting BTA in combination with liraglutide (a glucagon-like peptide-1 agonist used to treat diabetes and chronic obesity) than BTA alone [ 13 ]. Multiple other studies have reported on the benefits of combining BTA intragastric injections with low-calorie diet [ [14] , [15] , [16] ]. In a study from Jordon, the authors noted that although BTA injections are associated with lesser weight loss in comparison with gastric balloons, shorter procedure duration and fewer postoperative complications may make BTA injections a favourable treatment modality [ 17 ].…”
Section: Are Botulinum Injections Effective In Weight Loss?mentioning
confidence: 99%
“…Another retrospective study reported significant reduction in weight loss when injecting BTA in combination with liraglutide (a glucagon-like peptide-1 agonist used to treat diabetes and chronic obesity) than BTA alone [ 13 ]. Multiple other studies have reported on the benefits of combining BTA intragastric injections with low-calorie diet [ [14] , [15] , [16] ]. In a study from Jordon, the authors noted that although BTA injections are associated with lesser weight loss in comparison with gastric balloons, shorter procedure duration and fewer postoperative complications may make BTA injections a favourable treatment modality [ 17 ].…”
Section: Are Botulinum Injections Effective In Weight Loss?mentioning
confidence: 99%
“…The ethics approval number (210202) in [ 1 ] is also reported in several articles by some of the same authors, including [ 3 7 ], which describe studies and patient cohorts different to those reported in [ 1 ]. Additionally, discrepancies were identified between the description of the study design in [ 1 ] and the ethics approval documentation provided during discussions.…”
mentioning
confidence: 99%
“…Hence, the article does not adhere to the journal's second publication criterion or PLOS' Editorial policies pertaining to text reuse and publication of related studies, and concerns remain regarding partial redundancy of the two articles [1,2].The ethics approval number (210202) in [1] is also reported in several articles by some of the same authors, including [3-7], which describe studies and patient cohorts different to those reported in [1]. Additionally, discrepancies were identified between the description of the study design in [1] and the ethics approval documentation provided during discussions.The first author stated that the same approval number (210202) was obtained for multiple different studies [1,[3][4][5][6][7] as the applications for approval for all the studies were made to the IRB together. They also acknowledged that the study described in [1] was retrospective, which conflicts with the description of the study design in [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation